Influence of Capsule Content on the Structure and Mechanical Properties of Epoxy Resin Coating - HUANG Bing-li, MA Yong-quan (Cailiao Baohu)
In order to improve the mechanical properties of building anti-corrosion epoxy resin coating, the self-repairing building anti-corrosive coating was prepared by adding capsule into epoxy resin.Besides, the change of mechanical properties of the coating caused by the capsule were studied and the self-repairing effect of the coating was tested.Results showed that no cracks were generated in the coating, and the dense tissue was obtained.The capsule kept intact shape and structure in the coating, and no damage or bonding occurred.When the capsule content was increased, the hardness of the coating remains basically constant, and the impact strength and tensile strength of the coating first increased and then decreased.When 4% capsule was added, the impact strength and elongation strength of the coating were increased by about 18.0% and 13.9%, respectively, which significantly improved the repair speed of the cracks, and could play a more efficient repair role on the cracks of the coating.Therefore, a coating with higher restorative capability was generated when the adding amount of capsules was increased.The comprehensive analysis showed that the coating was best when the capsule proportion in the coating was 4%.